1998
DOI: 10.1097/00005650-199806000-00009
|View full text |Cite
|
Sign up to set email alerts
|

How Valid Are Medical Records and Patient Questionnaires for Physician Profiling and Health Services Research?

Abstract: The validity of the medical record and patient questionnaire for measuring delivery of different health services varied with the service. This report can be used to choose the optimal nonobservational method of measuring the delivery of specific ambulatory medical services for research and physician profiling and to interpret existing health services research studies using these common measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
243
3
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 283 publications
(255 citation statements)
references
References 43 publications
7
243
3
2
Order By: Relevance
“…The 117 consultations had a median length as reported by doctors of 10 min (interquartile range [5][6][7][8][9][10][11][12][13][14][15]. Patient questionnaires were returned in a median time of 7 days following the consultation (interquartile range 5-12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 117 consultations had a median length as reported by doctors of 10 min (interquartile range [5][6][7][8][9][10][11][12][13][14][15]. Patient questionnaires were returned in a median time of 7 days following the consultation (interquartile range 5-12).…”
Section: Resultsmentioning
confidence: 99%
“…5,14 Comparison with direct observation has suggested that patient reports may in some respects give a more accurate picture of a primary care consultation than medical records. 15,16 Of course, whether it is possible to measure the ÔtruthÕ about what happens in a consultation, even using direct observation or review of medical records, is debatable: one study which used direct observation by a research nurse as a gold standard found that the sensitivity of the medical record for documenting referrals, for example, was only 58%, while the Ôgold standardÕ itself only had an inter-rater reliability of 0.76 for recording referrals. 15 Previous studies have not considered how patient expectations are related to the disagreement between doctor and patient, or conversely how this disagreement might affect our view of how often patient expectations are met, although these issues are important in the interpretation of studies dealing with fulfilment of patient expectations.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that the medical record itself may have a substantial number of errors. (30)(31)(32) Because we use the medical record as the "gold standard" to which we compare self-report, it is possible that this assessment also has error. For some of the diseases the sample size of the inaccurate reporters was small which may have contributed to the lack of associations due to a lack of power to measure a difference between the inaccurate and accurate self-reporters.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22] Symptom research has looked at patient-clinician agreement of symptoms related to angina pectoris, 23 myocardial infarction, 24,25 psychological and somatic disorders, 8,[26][27][28][29] HIV infection, 30 and cancer. 31,32 One study found fair to substantial agreement between adult selfassessment and clinician assessment on the symptoms related to 'strep throat'.…”
Section: Introductionmentioning
confidence: 99%